Dilematics of Domestic Husbands in Marriage in Singapore (Maqashid Sharia Perspective) - Syukri Albani Nasution, Muhammad; Khadijah Binte Mahfuh, Siti (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2024)
This study examines the phenomenon of domestic husbands in marriage in Singapore using the perspective of maqasid al-shari'ah, to understand the dilemma of the role of husbands in modern families. The main objective of this study is to explore the reasons behind the change in the role of the husband, who was previously the main breadwinner, to be the husband of the household, as well as how this relates to Islamic principles that emphasize family welfare. Through a quantitative and qualitative approach, this study analyzed interviews with several part-time and full-time working domestic husbands, as well as a survey that explored the social, economic, and cultural factors that influence these changes. The results of the study show that the role of the husband in the household not only includes financial responsibility, but also social, emotional, and spiritual aspects in shaping family well-being. In the perspective of maqasid al-shari'ah, the husband's responsibility is more than just financial support, but also includes the maintenance and protection of the family in various dimensions of life. This study provides new insights into understanding the role of domestic husbands in the context of modern families in Singapore, as well as the relevance of the application of maqasid al-shari'ah in the face of evolving social dynamics.